Effects of resistance exercise training on the structure and function of cardiac, pulmonary and skeletal muscle tissues in rats with experimental pulmonary arterial hypertension - Soares, Leôncio Lopes (Universidade Federal de Viçosa, 2022)
The general objective of this work was to evaluate the effects of low- to moderate- intensity resistance exercise training (RT) on the structure and function of pulmonary, cardiac and skeletal muscle tissues in the stable pulmonary artery hypertension (PAH) model induced by monocrotaline (MCT) in rats. In the first study we focused on evaluating the effects of RT on the structure and oxidative stress of the lung and biceps brachii, as well as on the function, structure, single myocyte contractility and gene and protein expression in the right ventricle (RV). Male Wistar rats were randomly divided into groups: sedentary hypertension until failure; exercise hypertension until failure; sedentary control; exercise control; sedentary hypertension; and exercise hypertension. PAH was induced by two MCT injections (20 mg/kg, with 7 days interval). After the first MCT injection, animals in the exercise groups were submitted to a low- to moderate-intensity RT protocol (Ladder climbing; 55-65% of the maximal carrying load), 5 times/week, during the experimental period. Echocardiographic examination and physical effort tolerance test were carried out at specific time points of the experimental period. After euthanasia, lung, heart, and biceps brachii were dissected, weighed, and processed for histological, single myocyte, and biochemical analysis. The results show that RT improved survival and physical effort tolerance (i.e., Maximum carrying load), mitigated the pulmonary artery resistance increase (i.e., TA/TE), and preserved cardiac function (i.e., Fractional shortening, ejection fraction, stroke volume and TAPSE). In addition, RT counteracted oxidative stress (i.e., CAT, SOD, GST, MDA and NO) and adverse remodeling in lung (i.e., Collapsed alveoli) and in biceps brachii (i.e., atrophy and total collagen) tissues. Moreover, RT retarded RV adverse remodeling (i.e., hypertrophy, extracellular matrix, collagen types I and III, and fibrosis) and impairments in single RV myocyte contractility (i.e., amplitude and velocity to peak and relaxation). Furthermore, RT improved the expression of gene (i.e., miRNA 214) and regulatory proteins of the intracellular Ca 2+ cycling (i.e., PLB ser16 ) as well as of pathological (i.e., α/β-MHC, and Foxo3) and physiological (i.e., Akt, p-Akt, mTOR, p-mTOR, and Bcl-xL) hypertrophy pathways in RV tissue. In conclusion, along with survival and physical effort tolerance enhancement, low- to moderate-intensity RT during the development of stable MCT-induced PAH postpones pulmonary artery resistance increases and prevents RV dysfunction, RV adverse remodeling and myocyte contractility deterioration in rats. In the second study, we investigated whether low- to moderate-intensity RT is beneficial to left ventricle (LV) and LV myocyte contractile functions in such model of stable PAH induced by MCT. Following the experimental design of the first chapter, the results showed that in conjunction with the improvements in survival and physical effort tolerance, RT mitigated the LV and cardiomyocyte contractility dysfunctions promoted by MCT by preserving the ejection fraction and fractional shortening, the amplitude of shortening, and the velocities of contraction and relaxation in cardiomyocytes. Resistance exercise training also prevented increases in LV fibrosis and type I collagen caused by MCT and maintained the type III collagen and myocyte dimensions reduced by MCT. In conclusion, low- to moderate-intensity RT benefits LV and cardiomyocyte contractile functions in rats during the development of stable MCT-induced PAH. Taken together, these results are of clinical relevance insofar as it indicates that low- to moderate-intensity RT may contribute positively to the health and survival of individuals with stable PAH. Keywords: Pulmonary hypertension. Heart failure. Ventricular dysfunction. Physical exercise. Exercise tolerance. Adverse remodeling. Isolated cardiomyocytes.

O objetivo geral deste trabalho foi avaliar os efeitos do treinamento físico resistido (TR) de baixa a moderada intensidade na estrutura e função dos tecidos pulmonar, cardíaco e muscular esquelético no modelo de hipertensão arterial pulmonar (HAP) estável induzida por monocrotalina (MCT) em ratos. No primeiro estudo nos concentramos em avaliar os efeitos do TR na estrutura e estresse oxidativo do pulmão e bíceps braquial, bem como na função, estrutura, contratilidade de cardiomiócitos isolados e expressão gênica e proteica no ventrículo direito (VD). Ratos Wistar foram divididos aleatoriamente em grupos: sedentário hipertenso até a falha; exercitado hipertenso até a falha; sedentário controle; exercitado controle; sedentário hipertenso; e exercício hipertenso. A HAP foi induzida por duas injeções de MCT (20 mg/kg, com intervalo de 7 dias). Após a primeira injeção de MCT, os animais dos grupos de exercício foram submetidos a um protocolo de TR de baixa a moderada intensidade (subida de escada; 55-65% da carga máxima carregada), 5 vezes/semana, durante o período experimental. O exame ecocardiográfico e o teste de tolerância ao esforço físico foram realizados em momentos específicos do período experimental. Após a eutanásia, pulmão, coração e bíceps braquial foram dissecados, pesados e processados para análise histológica, de cardiomiócitos isolados e bioquímica. Os resultados demonstram que o TR melhorou a sobrevivência e a tolerância ao esforço físico (ou seja, carga máxima carregada), mitigou o aumento da resistência da artéria pulmonar (ou seja, TA/TE) e preservou a função cardíaca (ou seja, fração de encurtamento, fração de ejeção, volume sistólico e TAPSE). Além disso, a RT neutralizou o estresse oxidativo (ou seja, CAT, SOD, GST, MDA e NO) e a remodelação adversa nos tecidos do pulmão (ou seja, alvéolos colapsados) e do bíceps braquial (ou seja, atrofia e colágeno total). Além disso, a TR retardou a remodelação adversa do VD (ou seja, hipertrofia, matriz extracelular, colágeno tipos I e III e fibrose) e prejuízos na contratilidade de miócitos isolados do VD (ou seja, amplitude e velocidade para pico e relaxamento). Além disso, a TR melhorou a expressão gênica (ou seja, miRNA 214) e proteínas reguladoras do ciclo intracelular de Ca 2+ (ou seja, PLB ser16 ), bem como de fatores patológicos (ou seja, α/β-MHC e Foxo3) e fisiológicos (ou seja, Akt , p-Akt, mTOR, p-mTOR e Bcl-xL) no tecido do VD. Em conclusão, juntamente com o aumento da sobrevivência e tolerância ao esforço físico, a TR de baixa a moderada intensidade durante o desenvolvimento de HAP induzida por MCT estável adia o aumento da resistência da artéria pulmonar e previne a disfunção do VD, remodelamento adverso do VD e deterioração da contratilidade dos miócitos em ratos. No segundo estudo, investigamos se a TR de baixa a moderada intensidade é benéfica para a função do ventrículo esquerdo (VE) e contratilidade dos miócitos do VE nesse modelo de HAP estável induzida por MCT. Seguindo o desenho experimental do primeiro capítulo, os resultados mostraram que em conjunto com as melhorias na sobrevivência e tolerância ao esforço físico, o TR atenuou as disfunções da contratilidade do VE e dos cardiomiócitos promovidas pelo MCT ao preservar a fração de ejeção e a fração de encurtamento, a amplitude de encurtamento, e as velocidades de contração e relaxamento em cardiomiócitos. O treinamento de força também preveniu o aumento da fibrose do VE e do colágeno tipo I causados pelo MCT e manteve as dimensões do colágeno tipo III e dos miócitos reduzidos pelo MCT. Em conclusão, o TR de intensidade baixa a moderada beneficia as funções contráteis do VE e dos cardiomiócitos em ratos durante o desenvolvimento de HAP estável induzida por MCT. Em conjunto, esses resultados são de relevância clínica na medida em que indicam que o TR de baixa a moderada intensidade pode contribuir positivamente para a saúde e sobrevivência de indivíduos com HAP estável. Palavras-chave: Hipertensão pulmonar. Insuficiência cardíaca. Disfunção ventricular. Exercício físico. Tolerância ao exercício. Remodelamento adverso. Cardiomiócitos isolados.
Efeitos do treinamento físico resistido na estrutura e função dos tecidos cardíaco, pulmonar e muscular esquelético em ratos com hipertensão arterial pulmonar
Keywords: Exercícios físicos; Hipertensão pulmonar; Estresse oxidativo; Insuficiência cardíaca; Ratos como animais de laboratório; Educação Física